MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Ganoderma formosanum— advances in biotechnological fermentation, bioactive metabolites, and health-promoting applications: a critical review (2017–2025) - Kitipong Assatarakul; Khanom Simarani; Chen-Che Hsieh; Shin-Ping Lin; Isaya Kijpatanasilp; Yueh-Hao Ronny Hung; Saeid Jafari; Kuan-Chen Cheng (Critical Reviews in Food Science and Nutrition, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Caffeic acid restores neurogenesis and synaptic integrity under glucolipotoxic stress by suppressing inflammation and pyroptosis - I-Ning Tsai; Xiang-Ning Xie; Ping-En Ko; Yung-Che Tsai; Ching-Chun Chen; Li-Sung Hsu; Chau-Jong Wang (Metabolic Brain Disease, 2026)

Influence of free surface on microwave-induced rock fracturing: An experimental and numerical study - Yanlong Zheng; Ziqiang Su; Gaofeng Zhao; Ping Che; Jianchun Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Biocontrol eggplant soft rot caused by Fusarium equiseti through Bacillus amyloliquefaciens and its lipopeptides - Ping Zhou; Xilang Yang; Ziyun Xu; Xiaowei Che; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (International Journal of Food Microbiology, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Boosting crop disease recognition via automated image description generation and multimodal fusion - Shufeng Xiong; Lanlan Wang; Yiming Zhang; Ping Dong; Bingkun Wang; Yinchao Che; Lei Shi; Haiping Si (Computers and Electronics in Agriculture, 2025)

Variation of flavor substance-producing microbiota in four seasons of Chinese liquor fermentation - Feng Liang; Zhiming Zhong; Shibo Ban; Ping Ma; Jing Hao; Jing Wu; Heqiang Huang; Fuhong Che; Qun Wu; Yan Xu (Systems Microbiology and Biomanufacturing, 2025)

Effect of water vapor on the structure and performance of silver catalysts for ethylene oxidation - Yandong Chu; Hongmei Liang; Qiang Lin; Haoyang Huang; Ping Che; Yongsheng Han (Chemical Engineering Journal, 2025)

Effects of the southwest vortex on the vertical structure of ozone in the Sichuan Basin in China - Huiqiong Ning; Hong Wang; Ping Kang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Wei Liu; Ping Wang; Huizheng Che (Atmospheric Pollution Research, 2025)

Estimating the Permeability–Depth Relation of Slate Formation for Geothermal Project - Xuan-Xinh Nguyen; Che-Wei Yeh; Tan-Minh Le; Jia-Jyun Dong; Chih-Hsi Liu; Chi-Ping Pan (Rock Mechanics and Rock Engineering, 2025)

Microwave-induced strength reduction and weakening mechanisms of basic rocks - Zhongjun Ma; Xiaobao Zhao; Han Li; Hanwen Liu; Yangwei Long; Yanlong Zheng; Ping Che (International Journal of Rock Mechanics and Mining Sciences, 2025)

Study on the contribution of the major desert groups on SDS weather in East Asia combining the model simulation and multiple observations - Huiqiong Ning; Hong Wang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Ping Wang; Hailin Gui; Jikang Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Study on Measurement Method and Influencing Factors of Surface Temperature for Rock Under Microwave Irradiation - Zhongjun Ma; Xiaobao Zhao; Shuo Yang; Yanlong Zheng; Yangwei Long; Ping Che (Rock Mechanics and Rock Engineering, 2025)

8 R -methoxy-9 R -hydroxyl-fumitremorgin C, a new diketopiperazine alkaloid from Haima cold seep-derived fungus Aspergillus fumigatus CYH-5 - Yi-Hao Che; Jun-Feng Wang; Xue-Feng Shi; Wen-Ping Ding; Zhi-Hui Xiao; Jia-Min Wu; Fa-Zuo Wang; Si Zhang (Natural Product Research, 2025)

Developing Striga resistance in sorghum by modulating host cues through CRISPR/Cas9 gene editing - Sirisha Kaniganti; Sudhakar Reddy Palakolanu; Benjamin Thiombiano; Jagadeesh Damarasingh; Pradeep Reddy Bommineni; Ping Che; Kiran Kumar Sharma; Todd Jones; Harro Bouwmeester; Pooja Bhatnagar-Mathur (Plant Cell Reports, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High-precision U-series dating of Panxian Dadong hominin site, Guizhou Province, southwestern China - Xiaochao Che; Fei Han; Xingsheng Zhang; Bo Cao; Ping Xiao; Guanjun Shen; Jianxin Zhao (Quaternary Science Reviews, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

The Multifaceted Roles of Hippo-YAP in Cardiovascular Diseases - Hao Wu; Yan-Nan Che; Qi Lan; Yi-Xiang He; Ping Liu; Ming-Tai Chen; Li Dong; Meng-Nan Liu (Cardiovascular Toxicology, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Enhancing miso production with optimized puffed-rice koji and its biological function evaluation - Shin-Ping Lin; Yu-Chieh Chou; Chiao-En Chen; Yen-Tso Lai; Chen-Che Hsieh; Tsung-Yu Tsai; Yun-Hsin Lin; Shella Permatasari Santoso; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2024)

Heating and Water Transport Behavior of Sandstones Under Microwave Irradiation - Qinhua Zhao; Yanlong Zheng; Jianchun Li; Ping Che; Xiaobao Zhao (Rock Mechanics and Rock Engineering, 2024)

Effect of storage on microbioa and enzyme proteomic profile of low-temperature Daqu - Feng Liang; Zhiming Zhong; Muyan Ma; Jing Hao; Ping Ma; Jing Wu; Heqiang Huang; Fuhong Che; Qun Wu; Yan Xu (Food Bioscience, 2024)

Experimental investigation and numerical modeling of effect of specimen size on microwave-induced fracturing of diorite - Zhongjun Ma; Yanlong Zheng; Fuxin Rui; Gaofeng Zhao; Jianchun Li; Ping Che (Minerals Engineering, 2024)

New diketopiperazine alkaloids from the Haima cold seep-derived fungus Toxicocladosporium sp. CYH-18 - Yi-Hao Che; Jun-Feng Wang; Wen-Ping Ding; Zhi-Hui Xiao; Xue-Feng Shi; Jia-Min Wu; Fa-Zuo Wang; Si Zhang (Phytochemistry Letters, 2024)

Agar-altered foaming bacterial cellulose with carvacrol for active food packaging applications - Anita Chandra Kusuma; Yu-Chieh Chou; Chen-Che Hsieh; Shella Permatasari Santoso; Alchris Woo Go; Hong-Ting Victor Lin; I.-Lun Hsiao; Shin-Ping Lin (Food Packaging and Shelf Life, 2024)

The application study of the revised IMPROVE atmospheric extinction algorithm in atmospheric chemistry model focusing on improving low visibility prediction in eastern China - Chen Han; Hong Wang; Yue Peng; Zhaodong Liu; Wenjie Zhang; Yang Zhao; Huiqiong Ning; Ping Wang; Huizheng Che (Atmospheric Research, 2024)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Combined effect of surface PM2.5 assimilation and aerosol-radiation interaction on winter severe haze prediction in central and eastern China - Yue Peng; Hong Wang; Xiaoye Zhang; Ping Wang; Siting Li; Zhaodong Liu; Wenjie Zhang; Huizheng Che (Atmospheric Pollution Research, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Oil palm yield prediction across blocks from multi-source data using machine learning and deep learning - Yuhao Ang; Helmi Zulhaidi Mohd Shafri; Yang Ping Lee; Shahrul Azman Bakar; Haryati Abidin; Mohd Umar Ubaydah Mohd Junaidi; Shaiful Jahari Hashim; Nik Norasma Che’Ya; Mohd Roshdi Hassan; Hwee San Lim; Rosni Abdullah; Yusri Yusup; et al. (Earth Science Informatics, 2022)

circ-Ncam2 (mmu_circ_0006413) Participates in LPS-Induced Microglia Activation and Neuronal Apoptosis via the TLR4/NF-κB Pathway - Kai Guo; Yulin Chang; Yutao Jin; Hong Yuan; Ping Che (Journal of Molecular Neuroscience, 2022)

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

Retraction Note: Coastal meteorological characteristics based on big data and financial tax optimization of urban enterprises - Zhou Li; Che Ping (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE: Coastal meteorological characteristics based on big data and financial tax optimization of urban enterprises - Zhou Li; Che Ping (Arabian Journal of Geosciences, 2021)

Schizocorticium gen. nov. (Hymenochaetales, Basidiomycota) with three new species - Sheng-Hua Wu; Chia-Ling Wei; Yu-Ping Chen; Che-Chih Chen; Siou-Zhen Chen (Mycological Progress, 2021)

Reclassification of Brevibacterium frigoritolerans DSM 8801T as Bacillus frigoritolerans comb. nov. Based on Genome Analysis - Guo-Hong Liu; Bo Liu; Jie-Ping Wang; Jian-Mei Che; Peng-Fei Li (Current Microbiology, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Sodium dodecyl sulfate-coated-cationized agroforestry residue as adsorbent for benzene-adsorptive sequestration from aqueous solution - Helen Kong; Norasikin Saman; Pei Nee Tee; Siew Chin Cheu; Shiow Tien Song; Khairiraihanna Johari; Jimmy Wei Ping Lye; Mohd Azizi Che Yunus; Hanapi Mat (Environmental Science and Pollution Research, 2019)

Model tests on thermo-mechanical behavior of an improved energy pile - Han-long Liu; Cheng-long Wang; Gang-qiang Kong; Charles W.W. Ng; Ping Che (European Journal of Environmental and Civil Engineering, 2018)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

First report of tobacco mosaic virus infecting Benincasa hispida in Jiangxi Province in China - Feng Zhu; Yang Kai Zhou; Ya Qian Zhao; Yan Ping Che; Zhao Lin Ji (Journal of Plant Pathology, 2018)

First report of cucumber mosaic virus infecting Arachis hypogaea in Jiangxi Province in China - Feng Zhu; Yan Ping Che; Yang Kai Zhou; Shi Chang Cheng; Zheng Liu; Zhao Lin Ji (Journal of Plant Pathology, 2018)

Evaluating the contribution of multi-model combination to streamflow hindcasting by empirical and conceptual models - Yen-Ming Chiang; Ruo-Nan Hao; Hao-Che Ho; Tsang-Jung Chang; Yue-Ping Xu (Hydrological Sciences Journal, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Escitalopram reversed the traumatic stress-induced depressed and anxiety-like symptoms but not the deficits of fear memory - Chen-Cheng Lin; Che-Se Tung; Yia-Ping Liu (Psychopharmacology, 2016)

Oxidative stress, apoptosis, and cell cycle arrest are induced in primary fetal alveolar type II epithelial cells exposed to fine particulate matter from cooking oil fumes - Ying Liu; Yan-Yan Chen; Ji-Yu Cao; Fang-Biao Tao; Xiao-Xia Zhu; Ci-Jiang Yao; Dao-Jun Chen; Zhen Che; Qi-Hong Zhao; Long-Ping Wen (Environmental Science and Pollution Research, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Engineering Pseudomonas putida KT2440 for simultaneous degradation of organophosphates and pyrethroids and its application in bioremediation of soil - Zhenqiang Zuo; Ting Gong; You Che; Ruihua Liu; Ping Xu; Hong Jiang; Chuanling Qiao; Cunjiang Song; Chao Yang (Biodegradation, 2015)

Aspirin and nonsteroidal anti-inflammatory drugs after but not before diagnosis are associated with improved breast cancer survival: a meta-analysis - Xuan-zhang Huang; Peng Gao; Jing-xu Sun; Yong-xi Song; Cheng-che Tsai; Jing Liu; Xiao-wan Chen; Ping Chen; Hui-mian Xu; Zhen-ning Wang (Cancer Causes & Control, 2015)

Therapeutic Efficacy of Neuro AiD™ (MLC 601), a Traditional Chinese Medicine, in Experimental Traumatic Brain Injury - Ming-Che Tsai; Ching-Ping Chang; Syue-Wei Peng; Kai-Sheng Jhuang; Yi-Hsien Fang; Mao-Tsun Lin; Thomas Chang-Yao Tsao (Journal of Neuroimmune Pharmacology, 2015)

VPA inhibits renal cancer cell migration by targeting HDAC2 and down-regulating HIF-1α - Feng-qiang Yang; Min Liu; Feng-ping Yang; Jianping Che; Wei Li; Wei Zhai; Guang-chun Wang; Jun-hua Zheng; Xi Li (Molecular Biology Reports, 2014)

Actinopolyspora dayingensis sp. nov., a novel halophilic actinomycete isolated from a hypersaline lake - Tong-Wei Guan; Hui-Ping Zhao; Zhen-Ming Che; Xiao-Ping Zhang; Li-Li Zhang (Antonie van Leeuwenhoek, 2013)

Isoptericola salitolerans sp. nov., a halotolerant filamentous actinobacterium isolated from a salt lake, China - Tong-Wei Guan; Yun Teng; Ling-Ling Yang; Xiao-Ping Zhang; Zhen-Ming Che (Extremophiles, 2013)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

Reversine, a 2,6-disubstituted Purine, as an Anti-cancer Agent in Differentiated and Undifferentiated Thyroid Cancer Cells - Shih-Che Hua; Tien-Chun Chang; Hau-Ren Chen; Chieh-Hsiang Lu; Yi-Wen Liu; Shu-Hsin Chen; Hui-I Yu; Yi-Ping Chang; Ying-Ray Lee (Pharmaceutical Research, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Role of nitric oxide in amphetamine-induced sensitization of schedule-induced polydipsic rats - Yia-Ping Liu; Che-Se Tung; Pai-Jone Lin; Fang-Jung Wan (Psychopharmacology, 2011)

Wake-promoting agent modafinil worsened attentional performance following REM sleep deprivation in a young-adult rat model of 5-choice serial reaction time task - Yia-Ping Liu; Che-Se Tung; Yu-Lung Lin; Chia-Hsin Chuang (Psychopharmacology, 2011)

Passenger thermal perceptions, thermal comfort requirements, and adaptations in short- and long-haul vehicles - Tzu-Ping Lin; Ruey-Lung Hwang; Kuo-Tsang Huang; Chen-Yi Sun; Ying-Che Huang (International Journal of Biometeorology, 2010)

Chronic treatment with monoamine oxidase-B inhibitors decreases cocaine reward in mice - Ming-Che Ho; Chianfang G. Cherng; Yen-Ping N. Tsai; Chih-Yuan Chiang; Jia-Ying Chuang; Shu-Fang Kao; Lung Yu (Psychopharmacology, 2009)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Developmental steps in acquiring competence for shoot development in Arabidopsis tissue culture - Ping Che; Sonia Lall; Stephen H. Howell (Planta, 2007)

Gene Expression Patterns During Somatic Embryo Development and Germination in Maize Hi II Callus Cultures - Ping Che; Tanzy M. Love; Bronwyn R. Frame; Kan Wang; Alicia L. Carriquiry; Stephen H. Howell (Plant Molecular Biology, 2006)

Differential expression of genes encoding 1-aminocyclopropane-1-carboxylate synthase in Arabidopsis during hypoxia - Hsiao-Ping Peng; Ter-Yun Lin; Ning-Ning Wang; Ming-Che Shih (Plant Molecular Biology, 2005)